Tackling the challenges of the Eastern Nile Basin with nexus solutions - Basheer, Mohammed; Messay, Mekdelawit; Ringler, Claudia (CGIAR, 2024)
Given the growing impacts of climate change and extreme weather events on water, energy, and food security and ecosystem health, we need to double down on better management of water resources. Integrated assessment models are increasingly called upon to assess not only the hydrological but also the economic and economy-wide impacts of water resource management strategies for key human development indicators, such as agricultural GDP, employment, and environmental flow availability. This webinar presents results from NEXUS Gains and related work in the Eastern Nile Basin that can help policymakers develop more impactful and integrated water solutions in a climate crisis.